PENGARUH SOCIAL MEDIA MARKETING, PRODUCT QUALITY DAN PRODUCT DIVERSITY TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING PADA UMKM TRY BAROKAH DI SITUBONDO - Arlina Nurul Qiftiya; Ediyanto Ediyanto; Randika Fandiyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The rapid growth of culinary Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has intensified market competition and accelerated the adoption of digital marketing strategies. Alongside technological advancements, marketing has evolved beyond conventional offline approaches toward social media-based marketing, accompanied by significant changes in consumer behavior. Consumers increasingly utilize social media platforms, particularly WhatsApp and Instagram, to obtain product information, compare available alternatives, and make purchasing decisions. This study aims to analyze and examine the effects of social media marketing, product quality, and product diversity on purchase decisions through consumer purchase intention as an intervening variable at Try Barokah MSME in Situbondo. The study population consisted of customers of Try Barokah MSME. The sample was selected using a non-probability sampling technique through purposive sampling based on predetermined criteria. Data analysis and hypothesis testing were conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 3.0. The results of the direct effect analysis reveal that social media marketing, product quality, and product diversity each have a positive and statistically significant effect on consumer purchase intention. Furthermore, social media marketing, product quality, and product diversity also exert positive and significant effects on purchase decisions. In contrast, consumer purchase intention has a positive but statistically insignificant effect on purchase decisions. The indirect effect analysis indicates that consumer purchase intention does not significantly mediate the relationships between social media marketing and purchase decisions, product quality and purchase decisions, or product diversity and purchase decisions, despite the positive direction of these indirect effects.